2013
DOI: 10.1590/s1808-16572013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Gyropsylla spegazziniana (Lizer & Trelles) (Hemiptera: Psyllidae) to Beauveria bassiana (Bals.) Vuill.

Abstract: Gyropsylla spegazziniana is one of the most prominent pest insects of yerba mate culture in all production regions in Brazil, Argentina and Paraguay. Natural enemies have been recorded on G. spegazziniana nymphs and adults, including the Zoophthora radicans entomopathogenic fungus. Since there are no reports of Beauveria bassiana, the aim of this study was to register its pathogenicity with respect to this insect in a laboratory setting. Yerba mate branches were kept in glass flasks with water and we infested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…In this context, studies conducted in Brazil have shown the potential of vegetal extracts (BARZOTTO, 2010;HAAS et al, 2010), and the entomopathogenic fungus Zoophthora radicans (Brefeld) has been observed on 90% of G. spegazziniana cadavers in Paraguay tea plantations in Brazil and Argentina (ALVES et al, 2009;SOSA-GÓMEZ et al, 1994). Additionally, the susceptibility of G. spegazziniana to Beauveria bassiana isolates was recently demonstrated for the first time, revealing encouraging results (ALVES et al, 2013). So, as done by Ugine et al (2013), this new interaction must be investigated not only for testing the virulence of the different isolates, but also for the biological characterization, assessing their microbial biocontrol potential.…”
Section: Introductionmentioning
confidence: 95%
“…In this context, studies conducted in Brazil have shown the potential of vegetal extracts (BARZOTTO, 2010;HAAS et al, 2010), and the entomopathogenic fungus Zoophthora radicans (Brefeld) has been observed on 90% of G. spegazziniana cadavers in Paraguay tea plantations in Brazil and Argentina (ALVES et al, 2009;SOSA-GÓMEZ et al, 1994). Additionally, the susceptibility of G. spegazziniana to Beauveria bassiana isolates was recently demonstrated for the first time, revealing encouraging results (ALVES et al, 2013). So, as done by Ugine et al (2013), this new interaction must be investigated not only for testing the virulence of the different isolates, but also for the biological characterization, assessing their microbial biocontrol potential.…”
Section: Introductionmentioning
confidence: 95%
“…Estas colonias pertenecieron principalmente a los géneros Alternaria, Rhizopus, Absidia, Mucor, Penicillium, Aspergillus y Fusarium (Figura 2). Asimismo, se logró aislar e identificar una cepa del hongo entomopatógeno perteneciente al género Beauveria como se muestra en la Figura 3 (12) .…”
Section: Resultados Y Discusiónunclassified
“…An initial study showed that G. spegazziniana is susceptible to Beauveria bassiana (Blas.-Criv.) (Hypocreales: Cordycipitaceae) (Alves et al 2013). Further screening identified a certain strain, B. bassiana (sensu lato) strain Unioeste 44, as being highly toxic to G. spegazziniana (Formentini et al 2015).…”
Section: Using Sticky Card Traps To Evaluate Entomopathogen Fungi Occurrence In Insect Populations: a Cautionary Talementioning
confidence: 99%